2007
DOI: 10.3748/wjg.v13.i10.1528
|View full text |Cite
|
Sign up to set email alerts
|

Stool-based DNA testing, a new noninvasive method for colorectal cancer screening, the first report from Iran

Abstract: We could detect colorectal cancer related genetic alterations by analyzing stool DNA with a sensitivity of 64% and 20% and a specificity of 95% and 100% for Long DNA and p16 respectively. A non-invasive molecular stool-based DNA testing can provide a screening strategy in high-risk individuals. However, additional testing on more samples is necessary from Iranian subjects to determine the exact specificity and sensitivity of these markers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 23 publications
0
32
0
Order By: Relevance
“…Different methods such as light 1989;Zhang et al 2012). Some of these approaches were ineffective due to difficulty in releasing DNA from cysts, and also due to the presence of many compounds in stool samples such as proteases, DNase, polysaccharides and bile salts, which degrade DNA and inhibit enzymatic reactions (Abbaszadegan et al 2007). The tpi gene locus for development of specific PCR assay was chosen in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different methods such as light 1989;Zhang et al 2012). Some of these approaches were ineffective due to difficulty in releasing DNA from cysts, and also due to the presence of many compounds in stool samples such as proteases, DNase, polysaccharides and bile salts, which degrade DNA and inhibit enzymatic reactions (Abbaszadegan et al 2007). The tpi gene locus for development of specific PCR assay was chosen in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Identification of G. duodenalis genotypes in clinical specimens as well as differentiation of Giardia at the assemblage and genotype levels have relied on the analysis of the SSU-RNA, b-giardin (bg), glutamate dehydrogenase (gdh), elongation factor 1-alpha (ef-1), triose phosphate isomerase (tpi) genes. Molecular approaches to further discrimination of G. duodenalis isolates are reliant on the efficient extraction of DNA from Giardia cysts (Abbaszadegan et al 2007;Machiels et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Abbaszadegan [106] et al reported that this test could detect CRC related genetic alterations by analyzing stool DNA with a sensitivity of 64% and 20% and a specificity of 95% and 100% for long DNA and p16 respectively. An abnormal stool DNA test correlated with a colonoscopically demonstrable abnormality in 49% of cases (34 of 69).…”
Section: Derivative Technique For Crc Screeningmentioning
confidence: 99%
“…Furthermore, the DNA recovered from the CRC patients stool was of high molecular weight, unlike fragmented apoptotic DNA recovered from the stool samples of colonoscopy negative individuals (Boynton et al, 2003). Increased amount of high molecular weight DNA (often referred as long DNA or L-DNA) in the stool of CRC patients may result from the decreased apoptosis of the intestinal epithelial cells and/or increased exofoliation of cancerous cells from the tumor(s) (Boynton et al, 2003;Abbaszadegan et al, 2007). Therefore, the differential presence of L-DNA in the stools of CRC patients may be used as a diagnostic marker for CRC (Boynton et al, 2003;Abbaszadegan et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Increased amount of high molecular weight DNA (often referred as long DNA or L-DNA) in the stool of CRC patients may result from the decreased apoptosis of the intestinal epithelial cells and/or increased exofoliation of cancerous cells from the tumor(s) (Boynton et al, 2003;Abbaszadegan et al, 2007). Therefore, the differential presence of L-DNA in the stools of CRC patients may be used as a diagnostic marker for CRC (Boynton et al, 2003;Abbaszadegan et al, 2007). The presence of the L-DNA can easily and reliably be detected by polymerase chain reaction (PCR), making this a sensitive, specific, and affordable CRC test for mass screening.…”
Section: Introductionmentioning
confidence: 99%